2007
DOI: 10.1007/s11606-007-0225-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multidisciplinary Rounds to Simultaneously Improve Quality Outcomes, Enhance Resident Education, and Shorten Length of Stay

Abstract: Resident-centered MDR is an effective process using no additional resources that simultaneously improves quality of care while enhancing resident education and is associated with shortened length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
96
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 20 publications
3
96
0
1
Order By: Relevance
“…12 The other used a pre-post study design which may not account for unmeasured confounders affecting LOS and cost. 13 A third, smaller study found no effect on LOS and cost with the use of IDR. 15 No prior study has evaluated the effect of IDR on LOS and cost in a nonteaching hospitalist service setting.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…12 The other used a pre-post study design which may not account for unmeasured confounders affecting LOS and cost. 13 A third, smaller study found no effect on LOS and cost with the use of IDR. 15 No prior study has evaluated the effect of IDR on LOS and cost in a nonteaching hospitalist service setting.…”
Section: Discussionmentioning
confidence: 95%
“…Two prior studies demonstrated a reduction in LOS and cost with the use of IDR. 12,13 One study was conducted approximately 16 years ago and included patients with a longer mean LOS. 12 The other used a pre-post study design which may not account for unmeasured confounders affecting LOS and cost.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Interdisciplinary rounds (IDR), also known as multidisciplinary rounds, provide a means to assemble hospital care team members and improve collaboration. [9][10][11][12][13] Prior research on the use of IDR has demonstrated improved ratings of collaboration, 11,12 but inconsistent effects on length of stay and cost. 10,12,13 Notably, the format, frequency, and duration of IDR in prior studies has been variable and no studies, to our knowledge, have evaluated teamwork performance during IDR.…”
Section: Discussionmentioning
confidence: 99%